"If everyone sits on their hands, nothing happens": A phenomenological analysis of protest as a reflection of personal and communal processes. (May 2022) - Yakhnich, Liat; Walsh, Sophie D.
Abstract: In 2015, a video of policemen beating up an Ethiopian-born first Lieutenant in the Israeli Defense Forces, was published by the Israeli media and triggered a massive protest against police brutality and discrimination of the Ethiopian community. The current study aimed to understand the meaning the members of the Ethiopian community attribute to the protest, and its' relation to their experiences within the Israeli society. The paper is based on data gathered through interviews with 19 young Ethiopian Israeli adults. The analysis revealed that the participants' interaction with Israeli society is characterized by a shared experience of discrimination and racism, which shaped their perception of protest as a means of speaking out, strengthening a collective identity and achieving feelings of empowerment. However, individual differences were found in the way the participants believed their protest should be conducted. Findings suggest that an understanding of protest should take into account not only shared group experience but also illuminate individual differences. Universalist understandings of protest should be widened to include an examination of how protest can inform us about the social and historical process of relations between a minority group and the majority group.